Safety of Esophagogastroduodenoscopy within 30 Days of Myocardial Infarction: A Retrospective Cohort Study from a Canadian Tertiary Centre - Fahad Al-Ebrahim; Khurram J Khan; Waleed Alhazzani; Ahmed Alnemer; Abdullah Alzahrani; John Marshall; David Armstrong (Canadian Journal of Gastroenterology)
Patients who experience gastrointestinal bleeding after myocardial infarction (MI) often have comorbidities that could place them at increased risk of complications if evaluative endoscopy were to be performed. Although esophagogastroduodenoscopy is considered to be generally safe in high-risk individuals, some post-MI patients may be more susceptible to a variety of cardiopulmonary complications. This cohort study examined cardiopulmonary safety in post-MI patients and evaluated specific predictors of complications of post-MI endoscopy.